2023
DOI: 10.1161/strokeaha.121.038407
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Endovascular Treatment in Large Vessel Occlusion Stroke With Mild Prestroke Disability: Results From the HERMES Collaboration

Abstract: Background: The clinical and economic benefit of endovascular treatment (EVT) in addition to best medical management in patients with stroke with mild preexisting symptoms/disability is not well studied. We aimed to investigate cost-effectiveness of EVT in patients with large vessel occlusion and mild prestroke symptoms/disability, defined as a modified Rankin Scale score of 1 or 2. Methods: Data are from the HERMES collaboration (Highly Effective Reper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…In anterior circulation stroke, cost-effectiveness of endovascular thrombectomy has been demonstrated in several studies, most recently also in patients with underlying with preexisting disabilities and low ASPECT scores ( 11 , 27 , 28 ). In data from the HERMES collaboration (Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials), thrombectomy was previously reported with lifetime cost savings of $23,203 and an outcome improvement of 6.79 vs. 5.05 QALYs in comparison to BMC ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In anterior circulation stroke, cost-effectiveness of endovascular thrombectomy has been demonstrated in several studies, most recently also in patients with underlying with preexisting disabilities and low ASPECT scores ( 11 , 27 , 28 ). In data from the HERMES collaboration (Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials), thrombectomy was previously reported with lifetime cost savings of $23,203 and an outcome improvement of 6.79 vs. 5.05 QALYs in comparison to BMC ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Probabilistic sensitivity analysis was conducted in 30,000 Monte Carlo simulations by adjusting input parameters based on their probability distributions in line with previous studies ( 14 , 21 , 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…MT was statistically associated with lower NIHSS at discharge (p=0.04), favorable NIHSS shift (p=0.03), and increased independence rates at discharge (p=0.03) as well as outpatient follow-up (p=0.04) [46]. In addition, from a health-economic standpoint, MT resulted in lifetime cost savings of $2821 (health care perspective) or $5378 (societal perspective) and an increment of 1.27 quality-adjusted life years compared with BMM alone, indicating dominance of additional EVT as a treatment strategy in patients with minor stroke [47].…”
Section: Undergoing Immediate Mtmentioning
confidence: 98%